POTENTIAL PRODUCTION OF FOOD COLORANT FROM COFFEE PULP - Indah Hartati*); Indah Riwayati,; Laeli Kurniasari (Prosiding SNST Fakultas Teknik, 2012)
Coffee pulp is the waste produced during the pulping operation of the coffee berries. Coffee pulp is reported as a good candidate of material for food colorant production. The food pigment found in coffee pulp is anthocyanin. The anthocyanin content in coffee pulp is reported up to 25 mg of monomeric anthocyanins/100 g of fresh pulp on a dry weight basis. As the fourth largest coffee producer in the world, Indonesia has the potency to produce food colorant from coffee pulp. There are several methods that can be applied in the separation of anthocyanins from coffee pulp. The methods are include solvent extraction, microwave assisted extraction, ultrasound assisted extraction, supercritical fluid extraction and enzymatics extraction. Further researchs are needed in order to find the suitable method for anthocyanins production from coffee pulp.Keywords: coffee pulp, food colorant, anthocyanin